Implementasi dan Pengembangan Model Teaching Factory di Pendidikan Vokasi - Wibowo, Khrisnatian Natano'el; Sohidin (Media Manajemen Pendidikan, 2025)
Teaching factory model learning is applied to create vocational education graduates who are competent and ready to work in facing the competitive labor market. The purpose of evaluating the implementation of the teaching factory is to determine the suitability of the implementation of the teaching factory with the guidelines for the implementation of the teaching factory. In addition, knowing the obstacles and solutions in their implementation according to the understanding of the teaching factory manager in the school. Using a qualitative approach with a case study on the Stigma Resto Teaching Factory by conducting interviews with PIC, Waka for Public Relations, and Waka for Curriculum. The interview was conducted to obtain information in the form of the main components of the teaching factory, namely the Block Schedule, Goods/Services Products, and Jobsheets. The information obtained shows that the implementation of the teaching factory is carried out according to the understanding and ability of managers who try to adopt the concept of the teaching factory model but are not fully in accordance with the Teaching Factory Implementation Guidelines of the Directorate of Vocational Development. The main obstacle is the lack of a common mindset between teachers and students in implementing TeFa ideally